Step 1: isolate the "x" by bring everything else to the other side
![-2x-10y=10\\-2x= 10 +10y\\x= -5 -5y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/esmzgi1s0zognri3ooxe5qua2zomi8a0f0.png)
Step 2: The equation found above is the equation x is equal to so you plug it into all the x's the original equation to find y
![-2 (-5 - 5y) -10y = 10](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7e2aq5xsk2ywahwml8sfaasecticj8ybn9.png)
![10 + 10y -10y = 10\\10y - 10y = 0\\0y = 0\\y = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hwvge79faw5d3dzd8m9c1yh5jlvlk33kzr.png)
Step 3: Plug in your newly found y (0) into the original equation to find the x
![-2x- 10(0) = 10\\-2x - 0 = 10\\-2x =10\\x = -5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/866vyfh94qw3u85nhz60tfr68bq0gkeq5d.png)
Hope this helped! Let me know if there is anything I need to clarify or explain more in depth!